Women of the Gulag : portraits of five remarkable lives - Gregory, Paul R. (Hoover Institution Press publication, 2013)
During the course of three decades, Joseph Stalin's Gulag, a vast network of forced labor camps and settlements, held many millions of prisoners. People in every corner of the Soviet Union lived in daily terror of imprisonment and execution. In researching the surviving threads of memoirs and oral reminiscences of five women victimized by the Gulag, author Paul R. Gregory has stitched together a collection of stories from the female perspective, a view in short supply. Capturing the fear, paranoia, and unbearable hardship that were hallmarks of Stalin's Great Terror, Gregory relates the storie.